Mirror actuation design for the interferometer control of the KAGRA gravitational wave telescope. (25th October 2017) - Michimura, Yuta; Shimoda, Tomofumi; Miyamoto, Takahiro; Shoda, Ayaka; Okutomi, Koki; Fujii, Yoshinori; Tanaka, Hiroki; Barton, Mark A; Takahashi, Ryutaro; Aso, Yoichi; Akutsu, Tomotada; Ando, Masaki; et al.
Abstract: KAGRA is a 3 km cryogenic interferometric gravitational wave telescope located at an underground site in Japan. In order to achieve its target sensitivity, the relative positions of the mirrors of the interferometer must be finely adjusted with attached actuators. We have developed a model to simulate the length control loops of the KAGRA interferometer with realistic suspension responses and various noises for mirror actuation. Using our model, we have designed the actuation parameters to have sufficient force range to acquire lock as well as to control all the length degrees of freedom without introducing excess noise.